A fast approach to discard false negative susceptible lettuce genotypes to Fusarium oxysporum f.sp. lactucae race 1. Issue 9 (21st July 2022) - Sanna, Martina; Gilardi, Giovanna; Gullino, Maria Lodovica; Mezzalama, Monica
Abstract: Fusarium oxysporum f. sp . lactucae (FOL), the causal agent of Fusarium wilt of lettuce, is a seedborne and soilborne pathogen that causes severe losses everywhere lettuce is cultivated. Genetic resistance is potentially the most effective strategy to control the pathogen, but susceptibility evaluation of breeding material with conventional methods carried out under controlled conditions require 3–5 weeks before symptoms severity can be accurately assessed on young plants. A race‐specific quantitative real‐time PCR (qPCR) protocol was developed and validated according to the international validation standard (EPPO, PM7/98) as an aid to speed up the process. The experiments were carried out on five lettuce cultivars grown in the greenhouse and four cultivars grown in microcosm with known levels of susceptibility to the pathogen. The qPCR test carried out on seedlings grown in the microcosm detected the pathogen already 7 days after the inoculation. However, the correlation between the n. cell/μl of the pathogen and the symptoms expression was reliable only at 14 days from the inoculation both, in the greenhouse and in the microcosm assay. A high quantity (from 2.9x10 2 to 1.9x10 3 cells/μl) of FOL race 1 corresponds to a high susceptibility of the cultivars and low quantity (0–56.9 cells/μl) is correlated to a resistant response of the cultivar.